2022
DOI: 10.1037/pspa0000291
|View full text |Cite
|
Sign up to set email alerts
|

Who would mourn democracy? Liberals might, but it depends on who’s in charge.

Abstract: Despite widespread support for the principles of democracy, democratic norms have been eroding globally for over a decade. We ask whether and how political ideology factors into people's reactions to democratic decline. We offer hypotheses derived from two theoretical lenses, one considering ideologically-relevant dispositions, and another considering ideologically-relevant situations. Pre-registered laboratory experiments combined with analyses of World Values Survey data indicate that there is a dispositiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 137 publications
0
2
0
Order By: Relevance
“…Nevertheless, recent studies suggest that there are differences at least in perceptions of threat, consistent with the proposed account (Brandt et al, 2021;Kahn et al, 2022): Right-wing conservative ideology tends to be associated with concern about terrorism, war, and immigration (i.e., threats to the normative order), while left-wing ideology tends to be associated with concern about poverty, climate change, inequality, and racism (i.e., threats to progressive values). Furthermore, Benjamin et al (2022) found that liberals were more distressed by low democracy than conservatives were, but this difference disappeared when the ruling party was liberal, which plausibly reduces the perceived threat to progressive values.…”
Section: A N T I De Moc R At Ic Pr Edi Spo Si T Ions On T H E L E F T...mentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, recent studies suggest that there are differences at least in perceptions of threat, consistent with the proposed account (Brandt et al, 2021;Kahn et al, 2022): Right-wing conservative ideology tends to be associated with concern about terrorism, war, and immigration (i.e., threats to the normative order), while left-wing ideology tends to be associated with concern about poverty, climate change, inequality, and racism (i.e., threats to progressive values). Furthermore, Benjamin et al (2022) found that liberals were more distressed by low democracy than conservatives were, but this difference disappeared when the ruling party was liberal, which plausibly reduces the perceived threat to progressive values.…”
Section: A N T I De Moc R At Ic Pr Edi Spo Si T Ions On T H E L E F T...mentioning
confidence: 97%
“…Furthermore, Benjamin et al. (2022) found that liberals were more distressed by low democracy than conservatives were, but this difference disappeared when the ruling party was liberal, which plausibly reduces the perceived threat to progressive values.…”
Section: Antidemocratic Predispositions On the Left And The Rightmentioning
confidence: 99%